Health Literacy Status and Understanding of the Prescription Instructions in Diabetic Patients - Shivangini Singh; Sahana Devadasa Acharya; Ashwin Kamath; Sheetal D. Ullal; Rathnakar P. Urval (Journal of Diabetes Research)
This study aimed to assess the health literacy (HL) of patients having diabetes mellitus, their understanding of prescription instructions (PI), and the correlation between HL and understanding of PI. A cross-sectional survey was conducted in 263 adult diabetic patients who were assessed for their understanding of route of intake of the prescribed medication(s), frequency of intake, number of medication(s) to be consumed each time, indication for the medication(s), and the relation of drug intake with food. The HL of the patients was assessed by using Rapid Estimate of Adult Literacy in Medicine, a screening test comprising of 66 health-related words. The number of correctly pronounced words was used to assign a grade-equivalent reading level. There was a significant difference in the understanding of PI in patients with low and high HL levels. A significant difference was observed between the mean total score for interpreting PI in patients with 7 or fewer years of education compared with the other groups with a higher educational status (P<0.001). To conclude, diabetic patients with low HL level will have difficulty in understanding PI. Hence, an alternative comprehensive strategy needs to be adopted in clinical practice in these patients to provide them the instructions to take medications properly.